MANAJEMEN LABA PERUSAHAAN KELUARGA INDONESIA - Have Zulkarnaen; Fatichatur Rachmaniyah; Hamidah Hamidah (J-MACC, 2022)
The purpose of this study is to test whether family ownership has an effect on earnings management in companies listed on the Indonesia Stock Exchange. The data collection method used purposive sampling. The companies used in this study found 70 companies per year from 2015 to 2017 with a total of 210 observational data. The variables used in this study were family ownership and earnings management. The research model used is the estimation of the use of panel data regression models with data taken from the financial statements of observation companies. There is 1 development model to test the hypothesis used in this study. The results of this study prove that family ownership has an effect on improving the earnings management of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017.